Ladislavella tumrokensis: The first molecular evidence of a Nearctic clade of lymnaeid snails inhabiting Eurasia. Issue 3 (3rd May 2016) - Vinarski, Maxim V.; Aksenova, Olga V.; Bespalaya, Yulia V.; Bolotov, Ivan N.; Gofarov, Mikhail Y.; Kondakov, Alexander V.
Abstract : In this study, we provide the first molecular evidence for a possible connection between freshwater mollusc faunas across the Bering Strait via the Beringian Land Bridge using data inferred from gastropods of the family Lymnaeidae. The gastropods collected from geothermal springs in the Tumrok Mountains, West Kamchatka, Russia, share the nuclear internal transcribed spacer 2 (ITS2) and the cytochrome oxidase subunit I gene (COI) haplotypes, thus being as sister to those recorded for lymnaeid snails in the Stagnicola elodes group from Canada and the USA. Two lymnaeid species, Lymnaea ( Orientogalba ) tumrokensis Kruglov and Starobogatov, 1985 and Lymnaea ( Polyrhytis ) kurenkovi Kruglov and Starobogatov, 1989, were described from the Tumrok geothermal locality, but actually they are morphological variations of a single taxon of subspecies rank re-classified here as Ladislavella catascopium tumrokensis . This subspecies is the first discovered representative in the genus, which formed a dwarf race in a geothermal habitat. Our findings highlight the possible exchange between freshwater faunas in Beringia during the Pleistocene and an important role of geothermal ecosystems as possible cryptic refugia for freshwater hydrobionts.